ASSOCIATIONS BETWEEN BODY MASS INDEX AND COGNITIVE CHANGE IN BLACK OLDER ADULTS. (11th November 2018) - Aiken-Morgan, A; Capuano, A; Arvanitakis, Z; Barnes, L
Abstract: Despite general negative health effects, elevated body mass index (BMI) can be protective against poor health outcomes, including cognitive decline, in old age. Few studies have examined these longitudinal relationships in Black older adults. The purpose of this study was to examine how baseline BMI and BMI classification group (i.e., underweight, normal, overweight, or obese) variables related to cognitive change in Black participants from the Minority Aging Research Study (N = 718, mean age = 73.6, mean education = 14.8). Mean BMI was 30.3 (SD = 6.6), with 33.1% overweight and 46.4% obese. Participants underwent clinical evaluations, including 19 neuropsychological tests; summary measures for 5 cognitive domains and global cognition were subsequently derived. In mixed effects models adjusted for age, sex, and education, higher BMI was associated with slower decline in global cognition (Est. = 0.002, SE = 0.001; p < .01) and three separate cognitive domains: episodic memory (Est. = 0.002, SE = 0.001; p < .05), semantic memory (Est. = 0.003, SE = 0.006; p < .01), and working memory (Est. = 0.002, SE = 0.001; p < .05). Next, mixed effects models examining BMI classification group and cognitive decline showed the same pattern of findings, along with two additional significant results for perceptual speed (Est = 0.011, SE = 0.005; p < .05) and visuospatial ability (Est = 0.014, SE = 0.005; p < .01). The present findings support the "obesity paradox, " where higher BMI status may offer late-life cognitive benefits. Future research should investigate underlying mechanisms.